(untitled) (Agricultural Engineering, 2018)
The article presents analysis of operation of Fao Far 6840 mini harvester for machine wood harvesting. Analysis was made based on working day timing. The investigations were carried out on the area of Lubliniec Forest Inspectorate, Bór Forestry on the habitat forest site − fresh mixed forest where pine wood was obtained with the use of a harvester. Timing was carried out based on the registration of the exploitation time of a harvester with the use of a video camera and stopwatch and measurements of the obtained size grade. Based on the obtained results low values of performance in the exploitation change time 9.61 m3·h−1, and effective performance 12.14 m3·h−1 were reported. Low machine performance was affected mainly by conditions of harvesting, low log volume (at the average 0.62 m3) and concentration of trees. The head structure (applied feed system), weak work organization (short time of a single 6 hour shift) and weak skills of the machine operator were additional factors that reduced the performance.